2017
DOI: 10.1007/s00405-017-4694-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intubation and tracheotomy in patients with deep neck infection

Abstract: Possible airway compromise further complicates treatment of deep neck infections (DNI). Airway management is crucial, but factors affecting the method of choice are unclear. We retrospectively evaluated adult DNIs in a single tertiary center covering 10 years, with special attention on airway management. Patient data were retrieved from electronic data files from 2007 to 2016, and included adult patients with DNI operated through the neck. Of the 202 patients, 127 (63%) were male, with a median age of 47 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…The rate for necrotising fasciitis was 0.7% in this study. Previously, Tapiovaara et al [7] observed that OI is the most common aetiology for deep neck infections with increased risk for mediastinal involvement. In their study, 12 of 25 patients (48%) who developed mediastinitis as a result of deep neck infections were assessed to be of dental origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate for necrotising fasciitis was 0.7% in this study. Previously, Tapiovaara et al [7] observed that OI is the most common aetiology for deep neck infections with increased risk for mediastinal involvement. In their study, 12 of 25 patients (48%) who developed mediastinitis as a result of deep neck infections were assessed to be of dental origin.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of clinical research, it is interesting that severe OIs have become more frequent in recent decades [1][2][3][4][5]. Deep neck infections are often caused by odontogenic foci [2,6,7], which may, in the most severe cases, be fatal [8]. Besides the need for treatment in intensive care, OIs may lead to infection complications and distant infections [2,7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with DNI and limited mouth opening, transnasal intubation with the guidance of a flexible fiberoptic bronchoscope may be attempted [55,56]. Tracheostomy is life-saving and early tracheostomy is recommended when massive upper airway edema potentially leading to a compromised airway, or a complicated clinical course without response to the initial treatment [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the 92 patients had tracheostomy performed at the primary stage of OI treatment; this patient did not develop nosocomial pneumonia during the ICU period. Tracheostomy has been thought to decrease complications related to longer intubation times in patients with deep neck infection according to the study of Tapiovaara et al [24]. In that study, patients were treated mostly for otolaryngological infections.…”
Section: Discussionmentioning
confidence: 99%